A Landscape in my mind - Sketching as embodied reinforcer of mental imagery - Ramos, M. (Drawing Heritage(s), 2019)
Drawing from fieldwork experience in Northern Ethiopia, and particularly from ongoing investigation of the meaning of monumental remains in rural areas of Bahir Dar and Gondar, I aim to present and discuss both the use of sketching as a phenomenological part of anthropological research and the role of this seemingly informal and non-analytical activity in my overall research. A number of heuristic, and indeed epistemological, difficulties are bound to arise from the clash between the semantic framework of the researcher and that of the communities studied, in what regards the understanding of tangibility and intangibility of a specific cultural heritage. To resort to sketching, in such context, is not necessarily meant as a tool to fully switch from a verbally-based cognitive device to a non-verbally-based one, but rather to both heighten the being-in-the-field observational qualities of the one trying to make sense of a novel set of knowledge challenges, and to offer a critically conscious verification stance regarding the categorial enclosures of language-based worldviews. The understanding of the afore-mentioned heritage, and its cultural significance, needs to take into consideration the profound and enduring religious, philosophical and linguistic gaps between Western worldviews and those of Northern Ethiopian Monophysite Christianity. I thus contend that the act of sketching in such context offers a way to procedurally bridge such gaps and to set the stage for a finer comprehension of the meanings of inscribed heritage in the Northern Ethiopian rural landscape.